2015
DOI: 10.1016/j.jacc.2015.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Vasa Vasorum Restructuring in Human Atherosclerotic Plaque Vulnerability

Abstract: VV increase with fibrous plaque volume and intraplaque neovessels with particular structures are associated with plaque vulnerability. Imaging for microvasculature could become a new window for plaque vulnerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 31 publications
2
40
0
1
Order By: Relevance
“…The most representative OCT findings indicating vulnerable plaques that may lead to acute coronary syndrome (ACS) are lipid-rich plaques and thin-cap fibroatheroma (TCFA), which are confirmed by histopathological analysis [8,9]. Furthermore, macrophage accumulation [10], microvessels within atherosclerotic plaques [11], and adventitial vasa vasorum [12] are known to be other indicators of vulnerable plaques. However, previous prospective trials evaluating plaque vulnerability by intravascular imaging demonstrated a low predictive value for subsequent lesion progression and future cardiovascular events [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…The most representative OCT findings indicating vulnerable plaques that may lead to acute coronary syndrome (ACS) are lipid-rich plaques and thin-cap fibroatheroma (TCFA), which are confirmed by histopathological analysis [8,9]. Furthermore, macrophage accumulation [10], microvessels within atherosclerotic plaques [11], and adventitial vasa vasorum [12] are known to be other indicators of vulnerable plaques. However, previous prospective trials evaluating plaque vulnerability by intravascular imaging demonstrated a low predictive value for subsequent lesion progression and future cardiovascular events [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…vasa vasorum, pericardial fat). Taruya et al reported that increased intraplaque neovessels were associated with coronary plaque vulnerability [5], suggesting possible relationship between coronary vasospasm and accelerated plaque instability in the current case. Previous studies have shown that diabetes promotes microangiopathic neovessels in the plaque, as well as in the retina [6], while statins prevented neovascularization in hypercholesterolemic pigs, independently of their cholesterol-lowering effect [7].…”
Section: Discussionmentioning
confidence: 70%
“…Neovascularization, the growth of vessels within the coronary wall, is an important factor in atherogenesis. OCT studies have shown that neovascularization is associated with thin fibrous caps, muted response to statin therapy, and plaque progression [92][93][94]. Taking advantage of OCT's high resolution has allowed investigation of fibrous cap morphology in plaque disruption, indicating that cap thinning at the shoulder of atheromas was commonly associated with disruption and that cap disruption tended to be directed against the direction of coronary flow [88,90,95].…”
Section: Clinical Studiesmentioning
confidence: 99%